Choledochoduodenostomy versus sphincteroplasty in the surgical treatment of common duct stones - Nusret AKYÜREK; Erdoğan SÖZÜER; Orhan USLU; Mustafa KEÇELİ; Yücel ARITAŞ (Turkish Journal of Gastroenterology, 2020)
-